Skeuomorphism in Aksumite Pottery? Remarks on the Origins and Meanings of Some Ceramic Types - Manzo, Andrea (Aethiopica, 2003)
This paper deals with the problem of the origins of some Aksumite ceramic types. The possibility that these types were originated by the imitation of shapes and decorations of imported Mediterranean metal and glass vessels is pointed out. Several cases supporting this hypothesis are proposed. Thus, Aksumite pottery can give us information about a class of imported luxury items absent in the archaeological record but present in the documentary sources, which did not escape the melting pot and re-use. As the use of metal vessels by the Aksumite elite might be linked to the adoption of Mediterranean elements in Aksumite pagan ideology, the imitation of metalware in less expensive media such as pottery suggests the adoption of this ideology by people of lower status. Moreover, the changes in ceramic styles in the mid-4th–mid-6th centuries A.D. can be related to the progressive adoption of Christianity.